2017
DOI: 10.1371/journal.pone.0188675
|View full text |Cite
|
Sign up to set email alerts
|

Human behaviours associated with dominance in elite amateur boxing bouts: A comparison of winners and losers under the Ten Point Must System

Abstract: Humans commonly ascertain physical dominance through non-lethal fighting by participating in combat sports. However, the behaviours that achieve fight dominance are not fully understood. Amateur boxing competition, which is judged using the subjective “Ten Point Must-System”, provides insight into fight dominance behaviours. Notational analysis was performed on 26 elite male competitors in a national boxing championship. Behavioural (guard-drop time; movement style [stepping/bouncing time]; clinch-time; intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…El‐Ashker and Davis et al report straight punches (jabs and crosses) to be the most prevalent punches in competition boxing, followed by hooks. Typical work rate for elite boxers under current AIBA competition rules ranges from 71 to 109 offensive and defensive actions per 3‐minute round of boxing (approximately 0.4‐0.6 actions per second), although work rates as high as 1.9 actions per second have been reported when including locomotive actions (ie, bouncing around the boxing ring) and clinching . As such, the 3MPT contains predominantly straight punches with additional hooks to reflect the specific punch types thrown in a bout, and the work rate was 126 actions per round (0.7 actions per second).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…El‐Ashker and Davis et al report straight punches (jabs and crosses) to be the most prevalent punches in competition boxing, followed by hooks. Typical work rate for elite boxers under current AIBA competition rules ranges from 71 to 109 offensive and defensive actions per 3‐minute round of boxing (approximately 0.4‐0.6 actions per second), although work rates as high as 1.9 actions per second have been reported when including locomotive actions (ie, bouncing around the boxing ring) and clinching . As such, the 3MPT contains predominantly straight punches with additional hooks to reflect the specific punch types thrown in a bout, and the work rate was 126 actions per round (0.7 actions per second).…”
Section: Methodsmentioning
confidence: 99%
“…The 3-minute punch test (3MPT) was developed based on previously reported work rates and punch frequencies 9,10 in amateur boxing competition. El-Ashker 11 and Davis et al 9,12 report straight punches (jabs and crosses) to be the most prevalent punches in competition boxing, followed by hooks.…”
Section: Protocol Design and Descriptionmentioning
confidence: 99%
“…On the other hand, clinches were more frequently used during the 1 versus 1 than during the 1 versus 4 condition. Similar to other striking combat sports (i.e., amateur boxing), it seems that the increase in clinching movements during the 1 versus 1 condition was used as a pacing strategy to avoid fatigue throughout bouts [ 17 ]. However, the findings of our study indicated that clinching was not the preferred option to draw a stoppage and gain a brief rest when the kickboxer was confronted by four different opponents (i.e., 1 vs. 4).…”
Section: Discussionmentioning
confidence: 99%
“…It seems also plausible to argue that the increased usage of defensive skills was not only for tactical ends in response to the opponent's actions but also as a strategy to pace effort and minimize fatigue. In this sense, Dunn et al [ 17 ] revealed that amateur boxers reduced the total number of attacks and increased guard drops as part of a pacing strategy approach to avoid fatigue throughout the bout. In this sense, Rydzik and Ambroży [ 4 ] showed that the high level of physical fitness underlies the optimal development of technique for kickboxing competitors.…”
Section: Discussionmentioning
confidence: 99%
“…Boxing is a combat sport, consisting of intermittent bouts of multi-directional, high-intensity activity, interspersed by 1-min periods of active and passive recovery over a specific number of rounds [ 1 ]. Amateur bout activity includes repeatedly striking an opponent (≥ 20 punches per minute) [ 1 , 2 ], evading of punches, and manoeuvring around a boxing ring, with an activity rate for male elite amateur boxers across 3 rounds of ~ 1.31 (s -1 ) [ 1 , 3 ]. This activity can induce a significant biomechanical and physiological demand, in addition to the substantial psychological and hormonal demand associated with combat [ 3 7 ].…”
Section: Introductionmentioning
confidence: 99%